REALITAS KEHIDUPAN BERAGAMA DI INDONESIA DALAM PERSPEKTIF METAFISIKA THOMAS AQUINAS: Sebuah Refleksi Filosofis-Teologis - Emil, Yohanis (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Religious life in Indonesia is an important aspect of people's life. However, in reality, religious life in Indonesia still faces various challenges, such as intolerance, discrimination and violence. Intolerance is an intolerant attitude towards different views or beliefs. Discrimination is unfair treatment of a person or group based on their religion. Violence is an action that causes physical or psychological harm to a person or group based on their religion. Thomas Aquinas' metaphysical perspective on religious life can provide useful insights for understanding and overcoming these challenges. Aquinas emphasized the importance of the nature or essence of a thing. This essence is something that is inherent in something and cannot change. In the context of religious life, this essence can be interpreted as basic values ​​that form the basis for good religious practice. Based on Aquinas' perspective, intolerance, discrimination and violence are religious practices that are not in accordance with its essence. These practices conflict with universal basic values, such as the values ​​of truth, goodness and justice. The purpose of writing this article is to reflect the reality of religious life in Indonesia from the metaphysical perspective of Thomas Aquinas. The method used in writing this article is a qualitative bibliographic method by searching books as primary sources and articles as secondary sources. The results found in writing this article are various problems in religious life in Indonesia which are basically a lack of awareness to use reason in believing. Finally, it can be concluded that respect for differences in religious life to create a harmonious relationship will be achieved if Indonesian people use reason in their faith.